Demonstration of fluorescence enhancement via Bloch surface waves in all-polymer multilayer structures. Issue 20 (9th May 2016) - Fornasari, Lucia; Floris, Francesco; Patrini, Maddalena; Comoretto, Davide; Marabelli, Franco
Abstract : An all-polymer photonic structure constituted by a distributed Bragg reflector topped with an ultrathin fluorescent polymer film has been studied. A Bloch surface wave resonance has been exploited to improve pumping efficiency and enhance the fluorescence signal. Abstract : An all-polymer photonic structure constituted by a distributed Bragg reflector topped with an ultrathin fluorescent polymer film has been studied. A Bloch surface wave resonance has been exploited to improve pumping efficiency. A strongly polarization and angle dependent fluorescence signal is found with respect to the light pumping beam and the emitted wavelength. Matching the most favorable condition for the pump coupling and the collection geometry, the signal obtained from the structure appears to be two orders of magnitude larger than the one of the bare emitting film.